Pengaruh Rasio Keuangan Terhadap Harga Saham Perusahaan Sektor Pertanian Yang Terdaftar di BEI Periode 2020-2023 - Agustin Wulandari; Hari Setiono; M. Bahril Ilmiddaviq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Financial report analysis functions to identify the weaknesses and strengths of a business so that the business can make the right decisions, as is the case with registered agricultural sector companies. The study aims to understand the influence of ROA, CR, DAR, TATO and EPS on stock prices. Understanding with a quantitative approach and multiple regression analysis methods using SPSS 2 software. The sample in the study consisted of 22 businesses that used purposive sampling techniques. Based on the research results, ROA, CR, TATO, and EPS partially all have a significant effect on stock prices, while DAR does not have an effect on stock prices in the agricultural sector. In addition, simultaneously ROA, CR, DAR, TATO, and EPS have a significant effect on the stock prices of agricultural sector companies listed on the IDX.